Psychological changes in successful completers of an HIV-tailored smoking cessation program: mood, attachment and self-efficacy. Issue 6 (3rd June 2022) - Wiebe, Stephanie A.; Balfour, Louise; Cameron, William D.; Sandre, Daniella; Holly, Crystal; Tasca, Giorgio A.; MacPherson, Paul A.
ABSTRACT: High rates of cigarette smoking is the leading contributor to the increasing risk of cardiovascular disease (CVD) among people living with HIV (PLH). Relapse rates among PLH who quit smoking are high among those receiving standard care, which may be due to several unique social and psychological challenges PLH face when they attempt to quit smoking. The purpose of the current study was to examine change in relevant psychological factors in a subgroup of participants (n = 14) who remained smoke-free at 6-months follow-up in an HIV-tailored smoking cessation counselling program (N = 50). We examined self-reported depressive symptoms, attachment style and self-efficacy across 5 time points (baseline, quite date, 4, 12 and 24 weeks). At study baseline, mean depression scores fell above the clinical cut off of 16 (M = 16.31; SD = 13.53) on the Centre for Epidemiological Studies – Depression (CES-D) scale and fell below the clinical cut off at 24 weeks post quit date (M = 13.36; SD = 10.62). Results of multi-level modeling indicated a significant linear reduction in depressive symptoms and a significant linear improvement in self-efficacy to refrain from smoking across study visits. These results suggest that positive change in mood and self-efficacy may be helpful for PLH who remain smoke-free during a quit attempt.